Genomic variations, pathogenicity and evolutionary genetics of Salmonella enterica serovar typhi / Yap Kien Pong - Yap, Kien Pong (2017)
Typhoid fever is an infectious disease of global importance and is caused by the etiologic agent, Salmonella enterica serovar Typhi (S. Typhi). This disease causes an estimated of 21.7 million infections and 217,000 deaths annually. S. Typhi is a human-restricted pathogen, and human-carriers are the main reservoirs. Although the completed S. Typhi genomes are available in the public domain, the true extent of genetic variations remains obscure. Thus, this study could potentially shed light on the genetic basis of S. Typhi. In the first part of this study, extensive comparative genomics analyses of S. Typhi strains isolated from different backgrounds were carried out. A comparative genomics analysis combined with phylogenomic analyses revealed that an outbreak strain (BL196) was closely related to a human carrier strain (CR0044) and possibly derived from a common ancestor. Further comparison with other completely sequenced S. Typhi genomes showed that the strains BL196 and CR0044 exhibited unusual genomic variations despite S. Typhi being generally regarded as highly clonal. The two genomes shared distinct chromosomal architectures and uncommon genome features. Mutations in the two highly related virulence-determinant genes, rpoS and tviE were detected in strains BL196 and CR0044. These proteins were further studied using protein modelling and molecular dynamics simulations, which revealed that the mutation in rpoS is stabilising, while that of tviE is destabilising, potentially leading to altered protein functions. These microvariations between the two highly related strains with distinct epidemiological characteristics provide novel insight into the genes optimisation of the pathogen for its successful adaptation and persistence in the host. On the contrary, the sporadic strain, ST0208 was found to be far more conserved in comparison with other strains. In the second part of the study, the global MLST distribution of S. Typhi was described by utilizing the genome sequences from the first part of the study together with the recently released, publicly available 1,826 S. Typhi draft genome sequences. The global MLST analysis confirms the predominance of two sequence types (ST1 and ST2) co-existing in the endemic regions. Interestingly, S. Typhi strains with ST8 are currently confined to the African continent. Comparative genomic analyses of ST8 revealed unique mutations in important virulence genes such as flhB, sipC, and tviD that may explain the genetic variations that differentiate between seemingly successful (widespread) and unsuccessful (poor dissemination) S. Typhi populations. Large scale whole-genome phylogeny demonstrated evidence of phylogeographical structuring and showed that ST8 may have diverged from the earlier ancestral populations of ST1 and ST2, in which later lost some of its fitness advantages, leading to poor worldwide dissemination. This study demonstrated for the first time the utility of large-scale genome-based MLST as a quick and effective approach to narrow the scope of in-depth comparative genomic analysis and consequently provided new insights into the fine scale of pathogen evolution and population structure. In summary, this study has contributed to the understanding of genetic blueprints of S. Typhi associated with different clinical outcomes, particularly the less studied, yet important human carrier strain. Besides, this study has discovered a number of important key genes, novel genes, and mutations related to virulence and pathogenesis of S. Typhi, which could have profound implications in disease control of S. Typhi and other species.